PENGARUH STRESS KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAERAH (BPKD) KABUPATEN GOWA - Ulfa Hidayati (J-MSDM (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2024)
The Effect of Job Stress and Organizational Culture on Employee abilty at the Gowa Regency Regional Financial Management Agency (BPKD) (Guided by Edy Jumady and Niken Probondani Astuti). This research aims to determine and analyze the effect of job stress and the effect of organizational culture on the at the Gowa Regency Regional Financial Management Agency (BPKD). Data collection used primary data obtained from questionnaires and documentation from 32 respondents, employees of the Regional Financial Management Agency (BPKD) of Gowa Regency. This sample is a saturated sample which makes the total population the total sample size. The results of the questionnaire have been tested for validity and reliability, and classical assumptions in the form of normality, heteroscedasticity and multicollinearity assumptions have also been tested. The data analysis methods used are descriptive statistical analysis methods, multiple linear regression and hypothesis test.